In-vitro compatibility evaluation of fungal mixed culture for bioconversion of domestic wastewater sludge - Molla, A H; Fakhru’l-Razi, A; Abd-Aziz, S; Hanafi, M M; Alam, M Z (Springer, 2001)
Six different fungal strains/isolates were selected after conducting a series of experiments of isolation and screening to evaluate their successful adaptation and growth to domestic wastewater sludge and its efficient bioconversion into compost. Two different fungi were grown in the same petri dish 4 cm apart in two culture media, potato dextrose agar (PDA) and malt extract agar (MEA). Fifteen different in-vitro interactions were studied and summarized according to five possible outcomes, i.e., mutual intermingling, partial mutual intermingling, inhibition at contact point, inhibition at a distance and replacement. The interaction of Trichoderma hazianums Rifai with Phanerochaete chrysosporium 2094 was identified as mutual intermingling. The partial mutual intermingling of T. hazianums with Mucor hiemalis Wehmer suggested compatibility of the two strains without showing any abnormal effects. Perhaps these two combinations may interact mutually in any mixed culture programme. The fungal strain Aspergillus versicolor Vuill performed as a strong repellent and all interactions exhibited deadlock/inhibition at a certain distance. The isolate RW-Pl 512 from the gill of a basidiomycete from a rotten wood stub actively replaced the strain M. hiemalis in in-vitro culture.